Implementation Of Islamic Communication Principles In Making Online Police Record Certificate Through Super Apps Precision Application In North Sumatra - Dharmawanto Dharmawanto; Rubino Rubino; Mailin Mailin (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to implement the principles of Islamic communication and public service communication implemented by the North Sumatra Regional Police (Polda) in making Police Record Certificate (SKCK) through the Super Apps Presisi application and describe the community's assessment of the Super Apps Presisi application related to services in making Police Record Certificate (SKCK) at the North Sumatra Regional Police. Qualitative method with descriptive approach is the method used in this study. The informant in this study was SKCK Service Personnel. Data were collected using interviews and documentation studies. In specific findings, it can be seen that the application of Islamic communication principles carried out by the North Sumatra Regional Police (Polda) in making Police Record Certificate (SKCK) through the Precision Super Apps application at the North Sumatra Regional Police (Polda) is in accordance with the principles of Islamic communication because the interaction that is established is in harmony with Islamic law and contains noble moral values.